CRM AS A TOOL FOR IMPROVING BUSINESS QUALITY - Shukla, Dr Priyanka; Tripathi, Dr Prashant (Innovative Research Thoughts, 2017)
Customer Relationship Management (CRM) is widely accepted as an effective approach for collecting, analyzing, and translating valuable customer information into managerial action. However, the potential of CRM has been investigated only in the context of existing products.In this competitive market, customer is the most important property in an organization. It is not surprising that customer relationship management is increasingly used by the organizations to support different type of their customer. Customer is asource of information which is necessary for implementation of marketing strategy. According to changes in market place and active participation of customers in communicating marketing activities, customer relationship management becomes important. Customer relationship management is a phrase that describes how a firm interacts with customers. Most people think of customer relationship management as a system to capture information about customers. However, that is only part of the picture. Customer relationship management involves using technology to gather the intelligence you need to provide improved support and services to your customers. We reviewed previous studies, and identify these benefits which will be affected on customers.This paper reviews therole of CRM in development of business along with the impact they provide in boosting the performance of the business.